Prevalence and antibiotic resistance of Staphylococcus aureus and Streptococcus agalactiae in family-owned dairy herds in the state of Minas Gerais, Brazil (Veterinária Notícias, 2020)
Bovine mastitis is the most frequent disease in dairy herds worldwide. This disease causes greateconomic losses to producers, industry and consumers, since there are direct implications in publichealth due to the zoonotic potential of some agents involved in its etiology and the presence ofantimicrobial residues in milk. Considering the multifactorial aspect of the disease and the importanceof milk production in family farming, knowledge of the agents involved in its etiology and thesusceptibility profiles to antimicrobials is of paramount importance. In this study, the prevalence ofStaphylococcus aureus and Streptococcus agalactiae in herds of family farms in the Campo dasVertentes region of Minas Gerais State, and the resistance of these pathogens to the antibiotics mostcommonly used in the treatment of mastitis in livestock dairy farmers were evaluated. The studyinvolved 200 properties, covering an area of approximately 12,564 km2. The prevalences ofpathogens were carried out through microbiological analyzes of milk samples from the bulk milk tank.The modified Baird-Parker Agar medium was used for the detection of S. aureus, and the modifiedEdwards Agar medium, enriched with 5% desfibrinated sheep blood was used for the detection of S.agalactiae. Disc diffusion technique was used to evaluate resistance to antibiotics. The results showedhigh prevalence of S. aureus pathogens (71.0%) and S. agalactiae (68.0%) in the farms studied withhigh levels of resistance and multidrug resistance. The results demonstrate that there are controlfailures measures to contagious mastitis in studied herds, pointing to the need for more effectivecontrol these pathogens and the more judicious use of antibiotics aiming to minimize the problem ofresistance to them.